Defect Nanostructure and its Impact on Magnetism of α‐Cr2O3 Thin Films. Issue 17 (28th March 2022) - Veremchuk, Igor; Liedke, Maciej Oskar; Makushko, Pavlo; Kosub, Tobias; Hedrich, Natascha; Pylypovskyi, Oleksandr V.; Ganss, Fabian; Butterling, Maik; Hübner, René; Hirschmann, Eric; Attallah, Ahmed G.; Wagner, Andreas; et al.
Abstract: Thin films of the magnetoelectric insulator α ‐Cr2 O3 are technologically relevant for energy‐efficient magnetic memory devices controlled by electric fields. In contrast to single crystals, the quality of thin Cr2 O3 films is usually compromised by the presence of point defects and their agglomerations at grain boundaries, putting into question their application potential. Here, the impact of the defect nanostructure, including sparse small‐volume defects and their complexes is studied on the magnetic properties of Cr2 O3 thin films. By tuning the deposition temperature, the type, size, and relative concentration of defects is tailored, which is analyzed using the positron annihilation spectroscopy complemented with electron microscopy studies. The structural characterization is correlated with magnetotransport measurements and nitrogen‐vacancy microscopy of antiferromagnetic domain patterns. Defects pin antiferromagnetic domain walls and stabilize complex multidomain states with a domain size in the sub‐micrometer range. Despite their influence on the domain configuration, neither small open‐volume defects nor grain boundaries in Cr2 O3 thin films affect the Néel temperature in a broad range of deposition parameters. The results pave the way toward the realization of spin‐orbitronic devices where magnetic domain patterns can be tailored based on defect nanostructures without affecting their operation temperature. Abstract : The defect nanostructure of α‐Cr2 O3 relying on positron annihilation spectroscopy and transmission electron microscopy is studied. These structural data are correlated with the magnetotransport spin Hall magnetoresistance measurements and direct imaging of antiferromagnetic domains using nitrogen‐vacancy scanning magnetometry. The impact of structural defects on magnetic microstructure and spin‐orbitronic properties of Cr2 O3 thin films is discussed.